2007
DOI: 10.1111/j.1467-9590.2007.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Lie Bäcklund Symmetries and Sign‐Invariants to Quasi‐Linear Diffusion Equations

Abstract: Consider the 1+1-dimensional quasi-linear diffusion equations with convection and source term u t = [u m (u x ) n ] x + P(u)u x + Q(u), where P and Q are both smooth functions. We obtain conditions under which the equations admit the Lie Bäcklund conditional symmetry with characteristic η = u xx + H (u)u 2x + G(u)(u x ) 2−n + F(u)u 1−n x and the Hamilton-Jacobi sign-invariant J = u t + A(u)u n+1x + B(u)u x + C(u) which preserves both signs, ≥0 and ≤0, on the solution manifold. As a result, the corresponding so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
(89 reference statements)
0
38
0
1
Order By: Relevance
“…The homotopy model (8) can be freely chosen. Later for simplicity, the following simple homotopy model is exclusively taken…”
Section: Approximate Homotopy Symmetry Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The homotopy model (8) can be freely chosen. Later for simplicity, the following simple homotopy model is exclusively taken…”
Section: Approximate Homotopy Symmetry Methodsmentioning
confidence: 99%
“…Usually, with a continuous differential equation, we can study its invariance, symmetry properties and similarity reductions by means of the Lie symmetry method [1,3]. In particular, for the mathematical models described by differential equations containing arbitrary elements (parameters or functions) which have been found experimentally and so are not strictly fixed, the symmetry approach allows one to simplify them which make the models admit a symmetry group with certain properties or the most extensive symmetry group [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to present presumably the form of CLBS to study scalar diffusion equation. CLBSs related to separation of variables [50], sign-invariants [21] and invariant subspace [22,23] have been proved to be very effective to classify and seek for symmetry reductions of the considered equations. These form of CLBS can be extended to study diffusion systems and new results will be involved.…”
Section: Examplementioning
confidence: 99%
“…Indeed, since in principle, one can determine any solution by a suitably clever choice of CLBS unless one explicit know all possible solutions. An alternative tactic, which seems more practical, is to specify the CLBS by external considerations, for example, one might try CLBSs related to separation of variables [50], sign-invariants [21] and invariant subspaces [22,23] for scalar diffusion equations.…”
Section: Introductionmentioning
confidence: 99%
“…The conditional Lie-Bäcklund symmetry (CLBS) method introduced by Zhdanov [9] and Fokas and Liu [10,11] firstly has been proved to be very powerful to classify equations or specify the functions appeared in the equations and construct the corresponding group invariant solutions. Furthermore, authors have shown that CLBS is closely related to the invariant subspace; namely, exact solutions defined on invariant subspaces for equations or their variant forms can be obtained by using the CLBS method [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Advances In Mathematical Physicsmentioning
confidence: 99%